Determinação de alterações na expressão gênica, fenótipos comportamentais e padrões neurobiológicos em ratos adultos com elevada e baixa atividade exploratória privados de sono paradoxal na adolescência - Lima, Camila Nayane de Carvalho (2016)
Temperament can be considered the basis of humor, behavior and personality, they have strong biological basis, early development of the individual. Evidences suggests that temperament and personality traits predispose to the mood disorders. Because of this, it is important to identify biological factors associated with various temperament characteristics, such as differences in gene expression and neurochemical markers to help further evidence related to the etiopathogenesis of mental disorders such as depression and BD. (HE) and low exploratory activity (LE) exposes or not paradoxical sleep deprivation in adolescence. In the evaluation of the neurobiological basis of temperament, HE and LE tests were selected according to their exploratory profile in an open field test, a model of mania induced by temperamental sleep deprivation was used. Behavioral tests for locomotor activity and exploratory analysis, anxiety, cognition, depression, gene expression investigation of the clock genes, oxidative stress and inflammation were evaluated. The results of this study show that as individual behavioral factors, the exploratory patterns can be characterized in rats. By doing a translation for the human being these exploratory patterns reflect temperamental characteristics that influence a variety of behaviors and neurochemical and genetic parameters in response to the environment. Thus, our results for a strong interaction between exploratory patterns in animals and stressful events in adolescence contributing to the development of behavioral control type depression or mania in adulthood, showing that a selection of animals based on their exploratory pattern may be an alternative Interesting for conducting research with models with translational validity in psychiatry.